2001
DOI: 10.1103/physrevlett.87.127001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Strong-Couplings-Wave Superconductivity inMgB2:B

Abstract: We have investigated a gap structure in a newly discovered superconductor, MgB2, through measurement of the (11)B nuclear spin-lattice relaxation rate, (11)(1/T(1)). (11)(1/T(1)) is proportional to the temperature (T) in the normal state, and decreases exponentially in the superconducting (SC) state, revealing a tiny coherence peak just below T(c). The T dependence of 1/T(1) in the SC state can be accounted for by an s-wave SC model with a large gap size of 2Delta/k(B)T(c) approximately 5 which suggests it is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
104
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(113 citation statements)
references
References 11 publications
9
104
0
Order By: Relevance
“…We measured the T dependence of the 11 B spin-lattice relaxation time, T 1 , in Samples 2 and 3 and found a metallic, T independent value of 1/(T T 1 )= 167±3 s −1 in agreement with Ref. [17] and [18]. It is possible that the difference in morphology and purity at the grain surfaces explains that the CESR signal intensity is almost constant in Sample 1 while it changes strongly in Sample 2 and 3.…”
supporting
confidence: 81%
“…We measured the T dependence of the 11 B spin-lattice relaxation time, T 1 , in Samples 2 and 3 and found a metallic, T independent value of 1/(T T 1 )= 167±3 s −1 in agreement with Ref. [17] and [18]. It is possible that the difference in morphology and purity at the grain surfaces explains that the CESR signal intensity is almost constant in Sample 1 while it changes strongly in Sample 2 and 3.…”
supporting
confidence: 81%
“…A weak inter-band impurity scat-tering but strong intra-band scattering can suppress the coherence peak. This has been investigated in MgB 2 33 where the coherence peak is also not easily observed experimentally 34 . Since the superconductivity in Fe-based superconductors is created by doping, it is reasonable to assume that disorder is stronger than that in MgB 2 .…”
Section: Fig 10mentioning
confidence: 97%
“…The T C is slightly higher than the theoretical upper limit predicted for phonon-mediated superconductivity [2], which had been widely accepted until the discovery of the cuprate superconductors. However, 11 B-NMR studies [3] and the B isotope effect [4] showed that MgB 2 is a conventional BCS superconductor.…”
Section: Introductionmentioning
confidence: 99%